2017
DOI: 10.3233/wor-172543
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serious psychological distress among slaughterhouse workers at a United States beef packing plant

Abstract: Abstract. BACKGROUND:Workers in the animal slaughter and processing industry in the United States experience high rates of occupational injury as well as stressful work conditions, yet mental health in this workforce remains largely unstudied. OBJECTIVE: To assess prevalence of serious psychological distress (SPD) in a sample of industrial US slaughterhouse workers. PARTICIPANTS: Workers at an industrial beef packing plant in Nebraska, United States (n = 137). METHODS: We interviewed workers using the Kessler-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Additionally, the processing portion (including slaughter and packing) of farm-to-fork production is inherently more dangerous than non-food system industries (24). Meat, dairy, and fish production is more dangerous than other food production, with relatively high levels of severe equipmentrelated and assault-related injuries, and more fatalities from assaults from co-workers and animals and exposure to harmful substances (24), together with increased psychological distress among slaughterhouse workers (25). Those on the processing line work in very close proximity where food safety and the risk of zoonotic disease direct hygiene practices, rather than personto-person disease spread.…”
Section: Covid-19 Effects On Human Welfarementioning
confidence: 99%
“…Additionally, the processing portion (including slaughter and packing) of farm-to-fork production is inherently more dangerous than non-food system industries (24). Meat, dairy, and fish production is more dangerous than other food production, with relatively high levels of severe equipmentrelated and assault-related injuries, and more fatalities from assaults from co-workers and animals and exposure to harmful substances (24), together with increased psychological distress among slaughterhouse workers (25). Those on the processing line work in very close proximity where food safety and the risk of zoonotic disease direct hygiene practices, rather than personto-person disease spread.…”
Section: Covid-19 Effects On Human Welfarementioning
confidence: 99%
“…Among the studies that focused on the prevalence of mental health issues, all were quantitative, utilizing self-report questionnaire measures, with acceptable or above Cronbach’s αs, and had a control or reference group. Two articles solely compared their findings against the national average (Lander et al, 2016; Leibler et al, 2017). Lipscomb and colleagues (2007) compared SHWs to individuals from the same community.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the relationship between ethnicity and anxiety, finding that non-Hispanic Whites were six times more likely to experience serious psychological distress. However, they attributed the finding to anxiety caused by their minority ethnicity status within the workplace (Leibler et al, 2017). Emhan and colleagues (2012) found that SHWs also had significantly higher levels of psychoticism, somatization, anger, and hostility compared with butchers and office workers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations